Wavelet-based damage identification of structures under unknown support excitations - Li, Jun; Hao, Hong; Chieng, L. (CRC Press, 2014)
This paper presents a damage identification approach for structures under unknown support excitations. A wavelet-based response reconstruction technique is developed for structures under support excitations, and is used to formulate the relationship between different locations of time-domain responses. Acceleration responses from a structure under support excitations are measured for damage identification with a sensitivity-based model updating method. Numerical studies on a seven-storey planar frame structure are conducted to verify the accuracy and effectiveness of the proposed damage identification approach. Damage identification is considered with the initial finite element of the structure and the measured responses from the damaged state under traffic-induced ground motions. Structural elemental stiffness factors are iteratively updated until the reconstructed responses match the measured ones as closely as possible. The damage is identified as a change in the stiffness parameters. Identified results demonstrated that the simulated damage locations and severities in the structure can be identified efficiently without or with noise effect.